Prevalensi Komplikasi Kematian Ibu Dengan Persalinan Sectio Caesarea Di RSUD Dr. H. Abdul Moeloek Pada Tahun 2019 - Agung Assirri; Risti Graharti; Intan Kusumaningtyas (CV. Jasa Sukses Abadi, 2026)
Maternal mortality is defined as the number of deaths in women that occur during pregnancy up to 42 days after delivery, caused by conditions directly related to pregnancy or its management, not by accidents or injuries. In Indonesia, the pattern of causes of maternal mortality over time has remained relatively constant, with hemorrhage, preeclampsia-eclampsia, and infection as the dominant factors contributing to high maternal mortality rates. One medical intervention that can help reduce the risk of maternal mortality is delivery by cesarean section (CS), especially in cases where the condition of the mother or fetus does not allow for vaginal delivery. This study aims to identify the prevalence of complications that cause maternal mortality in cesarean section deliveries at Dr. H. Abdul Moeloek Regional General Hospital. The research design used is a descriptive study with a qualitative approach. Secondary data were collected from patient medical records, and the sampling method used was total sampling, so that all 351 cases of C-section deliveries during the study period were analyzed. The results showed that there were 2 cases of maternal mortality out of a total of 351 C-section deliveries, or 0.57%. Both deaths were caused by postpartum hemorrhage (50%) and pre-existing heart disease (50%). These findings indicate that although the maternal mortality rate in CS deliveries at Dr. H. Abdul Moeloek Regional General Hospital is relatively low, risk factors such as hemorrhage and comorbidity still require special attention in delivery management.